Petrological Studies of the Yamato Meteorites Part2. Petrology of the Yamato Meteorites - Okada, Akihiko; Yagi, Kenzo; Shima, Makoto (1975)
P(論文) The result of the mineralogical and petrological studies of the Yamato (a), Yamato (b), Yamato (c), Yamato (d) and Yamato (g) meteorites is summarized as follows. The Yamato (a) meteorite is distinctly chondritic, and belongs to enstatite chondrite. This meteorite is metal- and sulfide-rich, and its silicate phase is composed mainly of nearly pure enstatite and clinoenstatite. The peculiar mineral composition shows that this meteorite was formed under an extremely reducing condition. The morphology and petrography of chondrules in the Yamato (a) meteorite suggest that they were formed by rapid quenching of liquid droplets. The Yamato (b) meteorite is nearly monomineralic consisting of bronzite, without chondrule. According to PRIOR's (1920) classification, the Yamato (b) meteorite belongs to hypersthene achondrite in calcium-poor achondrites. The Yamato (c) meteorite is chondritic, and is composed mainly of olivine with a fair amount of magnetite. This meteorite belongs to type III carbonaceous chondrite, and may have experienced an oxidative environment. The Yamato (d) meteorite is composed mainly of olivine, bronzite, nickel-iron and troilite, and belongs to olivine-bronzite chondrite. The Yamato (g) meteorite consists of olivine, bronzite and nickel-iron, and is referred to olivine-bronzite chondrite. departmental bulletin paper